FREUDIAN TRIPARTITE ON DETECTIVE FICTION: THE TOKYO ZODIAC MURDERS - Dina Amelia; Jepri Daud (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
Sigmund Freud’s theory of psychoanalysis developed in the 1940s as mentioned in Barry (2002) was applied to unravel the unconscious psyche of a fictional character in the novel Tokyo Zodiac Murders by Soji Shimada. Tokiko, the villain in the story has been experiencing abusive treatment from her father, stepmother, and stepsisters.  The traumas she has received during her life has led to her decision to commit a well-prepared murder that could not be solved for decades. The qualitative method helps to identify and elaborate every component of the unconscious psyche of the villain, especially the Id, Ego, and Super-Ego in the story. The findings show that Tokiko’s Ego keeps her alive and survive to plan revenge on her family. Meanwhile, her Super-Ego fails to restrain herself from feeding her desire to conduct the vicious murder. Therefore, Tokiko’s Id is responsible for her action which is triggered by her devastating experiences. Her character remains committed and faithful to herself.